EFEKTIVITAS RELAKSASI SELAMA KEHAMILAN TERHADAP PENURUNAN STRES, KECEMASAN IBU HAMIL DAN RESPON JANIN DALAM KANDUNGAN - Septianingrum, Yurike (Jurnal Ilmiah Kesehatan, 2015)
Prenatal stress and anxiety are conditions that were commonly experienced by pregnant women during pregnancy which can be at risk of preterm birth, fetal growth restriction, and low birth weight (LBW). This study aims to do a literature review of some RCTs measuring the effectiveness of relaxation during pregnancy to reduce prenatal stress, anxiety, and fetal responses. Samples were 217 pregnant women with gestational age 32-34 weeks and single fetal. Variables focused on prenatal stress and anxiety level were measured by level of cortisol, ACTH, Norepinephrine (NE), Epinephrine (E), and Fetal Heart Rate (FHR). Guided Imagery (GI) and Progressive Muscle Relaxation (PMR) were generally effective to reduce prenatal stress and anxiety compared with control group, but there are no reduce levels of cortisol, ACTH, NE, and E. Fetal heart rate (FHR) can not be measured because the statistic datas were not shown on detail. Relaxation techniques such as GI and PMR were proved to be effective to reduce prenatal stress and anxiety during pregnancy. Nurses should promote the implementation of GI and PMR as safe relaxation techniques for pregnant women to reduce prenatal stress and anxiety during pregnancy.